Effects of electroconvulsive therapy on certain attention tests in patients with schizophrenia - Kubra Orman; Sukru Kartalci; Fatma Kartal; Keri̇m Ugur (Medicine Science, 2022)
It is known that patients with schizophrenia have positive and negative symptoms, as well as deterioration in cognitive functions. The main objective of this study was to investigate the effects of electroconvulsive therapy (ECT) on certain attention tests in patients with schizophrenia. The study included 103 patients who were diagnosed with schizophrenia according to the DSM-5 diagnostic criteria (39 outpatients receiving antipsychotic treatment alone, 32 inpatients receiving ECT+antipsychotic treatment, and 32 inpatients receiving antipsychotic treatment alone) and 42 healthy volunteers. The Stroop and digit span tasks were used as attention tests. Disease severity was assessed using the Scales for the Assessment of Positive/Negative Symptoms. There was a significant deterioration in the Stroop 4 and Stroop time difference values in all the three patient groups. No significant deterioration was observed in the digit span test in any of the groups. The Stroop 4, Stroop time difference and Stroop spontaneous correction scores were found to be associated with both negative and positive symptoms in the ECT+antipsychotic treatment group. The Stroop spontaneous correction scores were associated with positive symptoms only in the group receiving antipsychotic treatment alone. The only significant improvement in the number of spontaneous corrections was observed in the ECT group after therapy compared to the baseline. However, no significant change was observed in the Stroop 4 and Stroop time difference results, which were impaired compared to the normal scores. In the group receiving only antipsychotic treatment, there were significant improvements in Stroop 4, Stroop time difference and number of spontaneous corrections after treatment. In this study, it was determined that ECT added to drug treatment had positive rather than negative effects on the patients' performance in attention tests, although not as much as drug treatment. However, it should be considered that the group in which ECT was added to treatment consisted of more severe cases. [Med-Science 2022; 11(2.000): 528-36]